Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/ijms.54860
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Ferric Citrate induced Ferroptosis in Non-Small-Cell Lung Carcinoma through the inhibition of GPX4-GSS/GSR-GGT axis activity

Abstract: The morbidity and mortality rates associated with non-small-cell lung carcinoma (NSCLC) are increasing every year, placing new demands on existing therapies and drugs. Ammonium ferric citrate (AFC) is often used as a food additive for iron supplementation; however, to our knowledge, no studies have investigated whether AFC can induce ferroptosis in NSCLC. In this study, we demonstrated that specific concentrations of AFC effectively inhibit the proliferation and invasion of lung cancer cell lines in vitro usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…These findings suggested that inhibition of circDTL induced apoptosis via the intrinsic pathway. Considering that most chemotherapeutic agents primarily induce apoptosis via the intrinsic route ( Wu et al, 2021 ), it might explain why the silencing of circDTL increased the chemosensitivity of NSCLC cells. Ferroptosis is a novel identified form of cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that inhibition of circDTL induced apoptosis via the intrinsic pathway. Considering that most chemotherapeutic agents primarily induce apoptosis via the intrinsic route ( Wu et al, 2021 ), it might explain why the silencing of circDTL increased the chemosensitivity of NSCLC cells. Ferroptosis is a novel identified form of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, blockage of GPX4 could overcome resistance to Lapatinib via promoting ferroptosis in NSCLC (Ni et al, 2021). Another study also found that ammonium ferric citrate induced ferroptosis via blockage of GPX4 in NSCLC cells (Wu et al, 2021). Interestingly, several researchers have found that non-coding RNAs also play essential roles in regulating ferroptosis (Wang et al, 2019;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Interactions between the rapamycin kinase and GPX4 targets may regulate autophagy-dependent ferroptosis in cancer cells. GPX4 downregulation enhances sensitivity to chemotherapy by promoting ferroptotic cell death [ 42 , 43 ]. Lipid peroxidation is positively regulated by ALOX5 and contributes to ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature [2,17,18,19], we found that the most appropriate FAC concentration for HT22 cells was 150 µM and incubated for 24h. This concentration was used as the stimulus concentration for subsequent experiments.…”
Section: Fac Signi Cantly Supressed the Proliferation Of Ht22 Cell Li...mentioning
confidence: 97%
“…3B) in HT22 cells. The characteristic of mitochondria in Ferroptosis is that the mitochondrial membrane thickens and the membrane density increases, which causes the mitochondria to depolarize [18], ferroptosis is also accompanied by increased autophagosomes [19]. We carried out the detection of intracellular ultrastructure (mitochondria and nucleus).…”
Section: Dex Alleviates Iron Overload and The Accumulation Of Ros Which Induced By Ferroptosismentioning
confidence: 99%